Experimental study of heat transfer coefficient for nanofluid with inserted tape - Nur Ashikin, Usri (2010)
This thesis deals with a study of heat transfer coefficient for nanofluid with inserted tape. Research and development for enhancement heat transfer using nanofluid shows positive reaction for increasing the rate of convection heat transfer. The main objectives of this thesis are to determine heat transfer coefficient for nanofluid with inserted tape through experiment. Also, this paper will compare the experimental value of heat transfer coefficient with pervious literature. The thesis described the methodology utilize and the expected result from the experiment. Reynolds number varies between 4 000 until 22 000 within turbulent region, on the other hands, nanoparticles used is Alumina, Al2Owith volume concentration of 0.5%. The dimension of the twisted tape inserts used is 5, 10, 15 and 83. From the experimental result, ratio of twist, H/D =10 for nanofluid provides higher Nusselt number for higher Reynolds number. Theoretically, H/D of 5 for nanofluid should have highest value of Nusselt number. Different result than theory is due to environment distraction. Using twist insert tape with nanofluid as working fluid, the value of Nusselt number is higher compare to previous literature of Nusselt number for nanofluid and water in plain tube by 33.51% and 42.17% respectively. The research paper concluded with tabulation from result and recommendation for further research.